Effects of the COVID-19 associated United Kingdom lockdown on physical activity in older adults at high risk of cardiovascular disease: a mixed methods perspective from the MedEx-UK multicenter trial - Elsworthy, Richard J.; Jong, Stephanie T.; Hanson, Sarah; Shannon, Oliver M.; Jennings, Amy; Gillings, Rachel; Siervo, Mario; Hornberger, Michael; Hardeman, Wendy; Mathers, John C.; Minihane, Anne-Marie; Aldred, Sarah (Frontiers in Public Health, 2024)
Introduction Physical inactivity and sedentary behaviour are linked to increased risk of cardiovascular disease, infections and dementia, as well as placing a significant economic burden on healthcare systems. The implementation of COVID-19 pandemic lockdown measures aimed at reducing virus transmission posed challenges to the opportunity to be physically active. This study investigates how the first UK COVID-19 lockdown affected objectively measured physical activity in older adults at higher risk of cardiovascular disease. Methods We studied 48 individuals aged 55-74 years (81.3% female) with self-reported PA levels < 90 min/week and a QRISK2 score ≥ 10 (indicative of a ≥ 10% risk of a major cardiovascular event in the next 10 years) without mild cognitive impairment or dementia. Physical activity data was collected using objective wrist-based activity monitors and analysed across three time periods, usual activity (pre-pandemic), the precautionary phase when the UK began advising on limiting social contact and finally during the first UK lockdown period was collected (27 January 2020 and 07 June 2020). Data was analysed using linear mixed effects model was used to investigate PA levels over the measured 12-week period. Effects of BMI, age, deprivation score and baseline PA levels on PA across the three measurement periods were also examined. Focus-group and individual interviews were conducted, and data were thematically analysed. Results Average daily step count (−34% lower, p < 0.001) and active energy expenditure (−26% lower, p < 0.001) were significantly lower during the precautionary period compared with the usual activity period. Physical activity remained low during the UK lockdown period. Participants with a lower BMI engaged in significantly more (+45% higher daily steps p < 0.001) physical activity and those over 70 years old were more physically active than those under 70 years across the 12-week period (+23% higher daily steps p < 0.007). The risk of COVID-19 infection and restrictions because of lockdown measures meant some individuals had to find alternative methods to staying physical active. Participants described a lack of access to facilities and concerns over health related to COVID-19 as barriers to engaging in physical activity during lockdown. For some, this resulted in a shift towards less structured activities such as gardening or going for a walk. Discussion The data presented shows that lockdown measures during the COVID-19 pandemic significantly reduced physical activity among older individuals at risk of cardiovascular disease, particularly those with a higher body mass index. To support this population group in staying active during future lockdowns, a multifaceted strategy is needed, emphasizing psychosocial benefits and home-based physical activity. The MedEx-UK study was pre-registered with ClinicalTrials.gov (NCT03673722).